Impact of gadoxetic acid (Gd‐EOB‐DTPA)‐enhanced magnetic resonance on the non‐invasive diagnosis of small hepatocellular carcinoma: a prospective study. Issue 3 (2nd December 2012) - Granito, A.; Galassi, M.; Piscaglia, F.; Romanini, L.; Lucidi, V.; Renzulli, M.; Borghi, A.; Grazioli, L.; Golfieri, R.; Bolondi, L.
Summary Background Gadoxetic acid (Gd‐EOB‐DTPA) is a 'hepatocyte‐specific' contrast agent for magnetic resonance (MR) in both the vascular and the hepatobiliary phases. Aim To evaluate the contribution of the hepatobiliary phase of Gd‐EOB‐DTPA MR in the diagnosis of small hepatocellular carcinoma (HCC) in cirrhotic patients under surveillance. Methods Between 2008 and 2011, 48 consecutive small (10–30 mm) liver nodules were detected in 33 patients, who prospectively underwent contrast‐enhanced ultrasound (CEUS), Gd‐EOB‐DTPA‐enhanced MR and helical‐computed tomography (CT) in a blind study. The diagnosis of HCC was established according to AASLD 2005 criteria. Results Of the 48 nodules, 38 (79%) were diagnosed as HCC, 24 (63%) of them based on AASLD non‐invasive criteria, 11 diagnosed at histology and 3 during follow‐up. The typical vascular pattern (arterial hypervascularisation and venous/late washout) was detected in 30 (79%) HCC nodules by MR, in 22 (58%) by CT and in 17 (45%) by CEUS. Hypointensity during the MR hepatobiliary phase was observed in all HCC nodules and in 3 nonmalignant nodules (sensitivity 100%, specificity 70%, positive predictive value 93%, negative predictive value 100%, positive likelihood ratio 3.33, negative likelihood ratio 0). Eight (21%) of the 38 HCC nodules, 7 of which lacked the typical vascular features at any of the imaging modalities, showed washout in the portal/venous phase and hypointensity in the hepatobiliary phase at MRI, while this pattern was not detected in any nonmalignant lesion. Conclusions Gadoxetic acid magnetic resonance may enhance the sensitivity of the non‐invasive diagnosis of small hepatocellular carcinoma nodules in cirrhotic patients under surveillance. Double hypointensity in the portal/venous and hepatobiliary phases could be considered a new magnetic resonance pattern, highly suggestive of hypovascular hepatocellular carcinoma.